Adaptation and Validation of Mental Toughness-8 Measurement Tool in Indonesian Language: Confirmatory Factor Analysis (CFA) Study on College Students - Fevarine Weka Adina; Farida Harahap (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
At present, the mental toughness construct is attracting increasing attention as a measure of a person's resilience in facing pressure. One of the initiators of the mental toughness construct was Gucciardi and his team in 2015, who based it on existing mental toughness theories. This study was conducted to develop the mental toughness construct developed by Gucciardi and his team in the Indonesian context. This study was conducted using a quantitative method, with data collected via a questionnaire. A total of 114 people (87.7% women), with an average age of 22 years, who are currently studying at college, participated in this study. The collected data were analyzed using confirmatory factor analysis (CFA). Based on the CFA analysis, CFI = 0.956 and RMSEA = 0.071, indicating a mental toughness construct with a total of 8 good- and fit items in Indonesian. In addition, all the construct items are reliable, as the Cronbach’s alpha is 0.786 (≥ 0.70). It can be concluded that the Indonesian adaptation of the one-factor MT-8 model is a psychometrically sound and suitable instrument for evaluating mental toughness. Keywords: adaptation, CFA, mental toughness, reliability, validation